Insight into the orientation of LBG polymer films by XANES experiment and calculation. (August 2016) - Batchelor, D.R.; Aygül, U.; Dettinger, U.; Ivanovic, M.; Tournebize, A.; Mangold, S.; Forster, M.; Scherf, U.; Peisert, H.; Chassé, T.
Graphical abstract: Highlights: New polymers as organic photovoltaic candidates. Fitting of a direct theoretical XANES calculation. Two component azimuthal averaging and simple texture. Bulk sensitivity due to Sulphur K edge and fluorescence detection. Special experimental setup for fluorescence detection. Abstract: X-ray Absorption Near Edge Structure (XANES) has been used to investigate the orientation of polymers in thin films. These polymers contain Sulphur and are examples of Low Band Gap (LBG) materials; consequently, they are of interest for use in Organic Photovoltaic (OPV) devices. The characterisation of such films and in particular the determination of molecular orientation is essential for assessing important properties in potential devices, such as the charge mobility, energy transfer or charge separation. XANES is particularly useful in this respect giving information about both the orientation and the electronic structure. The technique was used recently to empirically determine the orientation of polymers in thin films and the study of changes associated with different processing conditions (e.g. [12, 13]). To obtain further insight into the near edge structure we use Density Functional Theory to calculate and fit to the experimental XANES spectrum and present the results for a few of the polymers studied.